The Effects of Punica granatum Flower Extract on Skin Injuries Induced by Burn in Rats. (19th January 2017) - Nasiri, Ebrahim; Hosseinimehr, Seyed Jalal; Akbari, Jafar; Azadbakht, Mohammad; Azizi, Soheil
Abstract : Background . We compared the efficacy of P. granatum (P) flower extract with that of silver sulfadiazine (SSD) for treating thermal burn injuries in rats. Methods . Ten Wistar rats in each group were topically given base cream, normal saline, cream containing 1% SSD, or creams containing 5% or 10% Punica granatum flower extract. The treatments were administered once daily until complete wound healing was observed. The wound area and healing time were assessed. In addition, percentage wound contraction and histopathological characteristics such as neovascularization and collagen formation were determined. The tannin content in P. granatum extract was determined. Results . The decrease in the average size of wounds on day 15 of the treatment was higher in rats treated with creams containing P. granatum extract than in rats treated with cream containing SSD (2.8 ± 0.9  cm 2 versus8.4 ± 3.2  cm 2 ). The wounds completely healed on day 25 of the treatment in rats treated with creams containing P. granatum flower extract compared with those in rats treated with the other agents. Conclusion . These results indicated that P. granatum flower extract promoted wound healing in rats and could be used for managing burn injuries.